RETTIE WILDING: LIFE TRAJECTORY OF THE PIONNER MEDICAL MISSIONARY IN THE CITY OF ANÁPOLIS AND REGION (1936-1986). (CIPEEX, 2022)
THE PRESENT RESEARCH AIMS TO STUDY THE LIFE TRAJECTORY IN SCIENTIFIC, PHILANTHROPIC AND EDUCATIONAL MEDICINE OF THE PIONEER MISSIONARY MEDICAL HENRIETTA BUCHAN WILDING (1889-1986), KNOWN AS RETTIE WILDING IN ANÁPOLIS AND ITS IMPORTANCE TO GOIS, BETWEEN 1936-1986 (CARVALHO, 2021, 2015; WILDING, 2020). THE OBJECTIVE OF THE RESEARCH INVOLVES THE CASE STUDY AND MEMORY ABOUT THE ROLE OF THE SCOTTISH MISSIONARY DOCTOR WHO, AFTER WORKING FOR SIX YEARS ON BANANAL ISLAND, AT THE TIME BELONGING TO GOIS, WHERE SHE STARTED A SMALL HOSPITAL, A LEPER COLONY, A SCHOOL AND A CHURCH, CAME TO WORK IN ANÁPOLIS-GOIS, BEING RECOGNIZED AS THE FIRST DOCTOR TO WORK IN GOIS. IT STARTS WITH THE FOLLOWING PROBLEM: WHO WAS RETTIE WILDING AND WHAT WAS HER CONTRIBUTION TO SCIENTIFIC MEDICINE, EDUCATION AND PHILANTHROPY IN ANÁPOLIS, WITH INFLUENCE IN GOIS BETWEEN 1936-1986? THE METHODOLOGY INVOLVES HISTORICAL AND SOCIOLOGICAL RESEARCH BASED ON MAX WEBER AND CHARTIER (WEBER, 2001; CHARTIER, 1990). COMPREHENSIVE SOCIOLOGY WORKS ON THE SUBJECTIVITY OF HISTORICAL SUBJECTS WHERE THEIR RELATIONSHIPS, ACTIONS AND INSTITUTIONS CREATED BY THEM MATERIALIZE OBJECTIVELY. IN THIS WAY, THE COLLECTION, ANALYSIS AND PRODUCTION OF CONTENT WILL TAKE PLACE THROUGH QUALITATIVE RESEARCH AND DOCUMENTS SUCH AS BOOKS, LETTERS, MINUTES OF CHURCHES AND INSTITUTIONS, THESES, MONOGRAPHS, NEWSLETTERS AND INTERVIEWS WITH FAMILY MEMBERS AND PROFESSIONALS WHO KNEW, WORKED OR WERE STUDENTS OF THE PERSON IN STUDY. EXPECTED RESULTS. THE COLLECTION OF DOCUMENTS WHICH WILL FORM PART OF THE CEDOCH/UNIEVANGLICA/AEE ARCHIVE; THE ABSTRACTION AND SOCIALIZATION OF KNOWLEDGE ACQUIRED THROUGH LECTURES, SYMPOSIA, NEWSPAPERS, ARTICLES, DOCUMENTARIES AND BOOKS, REVEALING THE IMPORTANCE OF THESE PROTESTANT PIONEERS IN ANÁPOLIS AND THEIR INFLUENCE IN THE REGION; MAY THIS EFFORT INSPIRE THOSE WHO WILL COME INTO CONTACT WITH THE MATERIAL PRODUCED, PUT UP WITH IT PROFESSIONALLY WITH A SENSE OF VOCATION, PIONEERING SPIRIT AND AS AGENTS OF SOCIAL TRANSFORMATION, MORE THAN JUST FULFILLING TASKS. CONCLUSION. THE MISSIONARY DOCTOR RETTIE WILDING WOULD BE ONE OF THE FIRST TO WORK WITH CLINICAL EXAMINATION AND LABORATORY IN ANÁPOLIS, AND PERHAPS IN GOIS (WILDING, 2020). SO, THERE IS A LACK OF KNOWLEDGE OF HEALTH AGENTS WHO ACTED IN AN INNOVATIVE AND INTENTIONAL WAY IN THE BRAZILIAN MIDWEST FROM SCIENTIFIC MEDICINE WITH ACTIONS THAT BROUGHT DEVELOPMENT TO THE PROMOTION OF HEALTH AND EDUCATION IN THE 20TH CENTURY. THE LIFE TRAJECTORY OF THESE PIONEERING AGENTS OF SOCIAL TRANSFORMATION IN HEALTH, EDUCATION AND SPIRITUALITY MADE ANÁPOLIS THE EPICENTER IN THE EXCHANGE OF ACTIONS THAT BENEFITED THE BRAZILIAN MIDWEST. A STORY THAT NEEDS TO BE KNOWN.